2019
DOI: 10.1186/s13756-019-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a sterile processing program in Northwest Tanzania: a mixed-methods study

Abstract: BackgroundInadequate training of health care workers responsible for the sterilization of surgical instruments in low- and middle-income countries compromises the safety of workers and patients alike.MethodsA mixed methods research study was initiated in the Lake Zone areas of Northwestern Tanzania in the summer of 2018. The goal was to identify the impact of education and training on sterile processing practices at ten hospitals. Quantitative data analyzed included hospital assessments of sterile processing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Nine papers discussed education, training and mentoring in relation to SP workers’ practice in LMICs. Shortcomings in education were identified as barriers to effective IPC and SP practice (Ayub Khan et al, 2018; Fast et al, 2017; Forrester et al, 2018c) but importantly also serve as opportunities to implement strategies to improve SP through education, training, and mentoring (Fast et al, 2018, 2019b, 2019a; Forrester et al, 2018a). Several authors presented the development and outcomes of SP educational initiatives.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine papers discussed education, training and mentoring in relation to SP workers’ practice in LMICs. Shortcomings in education were identified as barriers to effective IPC and SP practice (Ayub Khan et al, 2018; Fast et al, 2017; Forrester et al, 2018c) but importantly also serve as opportunities to implement strategies to improve SP through education, training, and mentoring (Fast et al, 2018, 2019b, 2019a; Forrester et al, 2018a). Several authors presented the development and outcomes of SP educational initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Costa et al (2018) noted that policy standards in Brazil required only cleaning, and not necessarily disinfection and sterilisation, before returning loaned instrument sets. During SP training and mentoring programmes in Ethiopian and Tanzanian hospitals, Fast et al (2019aFast et al ( , 2019b found that workers were apprehensive about using enzymatic detergents or soapy water in place of corrosive 0.5% chlorine solutions, a recommendation in alignment with recent changes to WHO (WHO and PAHO, 2016) evidence-based guidelines. In Ethiopia, this stemmed from differences between national guidelines and WHO global guidelines, while in Tanzania, implementing this practice change could have impacted accreditation from government inspectors, not all of whom had received and adopted recently updated guidelines.…”
Section: Challenges To Sterile Processing Practicementioning
confidence: 99%
See 3 more Smart Citations